Medicine Road - Henry, Will, 1912-1991. (New York : Leisure Books, 2007)
Mountain man Jim Bridger is counting on Jesse Callahan. He knows Callahan is the best mantolead the wagon train delivering guns and ammunition to Bridger's trading post at Green River. But Brigham Young has sworn to wipe out Bridger's posts, and he's hired Arapahoe warrior Watonga to capture those weapons at any cost.
Orphans of the North -- Medicine Road.
Originally published: Waterville, Me.: Five Star, 2006.
Keywords: Bridger, Jim, -- 1804-1881 -- Fiction; Young, Brigham, -- 1801-1877 -- Fiction; Indians of North America -- Fiction; Western stories